Implementing the Virtual Flipped Classroom (VFC) to Enhance Students’ Motivation in Learning English during Covid-19 Pandemic - Rochmawati, Desi; Martanti, Ika Fathin Resti; Yusuf, Munawir; Subagya, Subagya (STAIN Sultan Abdurrahman Kepulauan Riau, 2023)
Virtual Flipped Classroom (VFC) is a learning model that is suitable to be applied during the Covid-19 pandemic where the learning activities are mostly conducted online. The VFC in this study combines synchronous and asynchronous learning by using Schoology as the Learning Management System (LMS) and Zoom as the means to facilitate direct interaction between the lecturer and the students. This model was implemented to improve the student's motivation in learning English even in the pandemic situation. The objective of this study is to investigate the implementation of the VFC learning model to improve students’ motivation to learn. It is a qualitative study conducting action research. The participants were 47 students. The data were gathered by observation, sharing questionnaires, and interviews. The data were analyzed qualitatively, while the statistical data were used to support the qualitative data. The results showed that most of the students were motivated to learn English even though it was during the situation of pandemic Covid-19. They said that this model improves the students’ creativity, autonomous learning, and responsibility to have a self-learning process that motivated them in learning English